Management Analysis of Zakat, Infaq, Shodaqoh Fund Management in Improving Member Welfare at BMT Assyafi'iyah Berkah Nasional Rumbia Branch - Hani, Ummi; Khotamin, Nur Alfi; Mukhlishin, Ahmad (Universitas Islam Negeri Raden Intan Lampung, 2023)
Management The management of zakat, infaq, and shodaqoh (ZIS) funds of BMT Assyafi'iyah Berkah Nasional (BN) Rumbia Branch continues to spur economic growth of the community. One of them is by giving infaq. The infaq fund managed by BMT Assyafi'iyah BN Rumbia Branch is a fund distributed by muzakki. ZIS is a potential source of funds that can be used as an effort to realize people's welfare. The implementation of zakat involves a number of activities related to the management of zakat fund management, including: planning, organizing, implementing, and supervising the collection and distribution. The purpose of this study is to determine the management of ZIS funds in Baitul Maal Assyafi'iyahRumbia Branch, as well as to determine the improvement of member welfare. This type of research uses a qualitative descriptive approach. Data sources consist of primary and secondary data. Data collection techniques in this study used interviews, observation, and documentation as well as data analysis using an inductive approach. The management of ZIS fund management in Baitul Maal Assyafi'iyahRumbia Branch has been carried out according to the planned program, there are supporting and inhibiting factors in carrying out ZIS fund management management, but Baitul Maal Assyafi'iyah is able to overcome member difficulties that have an impact on member welfare.Keywords: Member Welfare, ZIS Fund Management Management